Post Merger Management : Value Creation in M & a Integration Projects. - Meynerts-Stiller, Kirsten (Emerald Publishing Limited, 2019)
This book pools the current know-how, and closes important knowledge gaps, to offer hands-on advice and practical answers to the many 'how to' questions relating to merger implementation. It provides a crucially important understanding of how to assess the chances of realising synergy potential and evaluate integration risks.